Diagnostic imaging and intervention of the musculoskeletal system: state of the art - Barile, Antonio; Reginelli, Alfonso; De Filippo, Massimo; Brunese, Luca; Masciocchi, Carlo (Acta Biomedica Atenei Parmensis, 2018)
The study of the musculoskeletal system has always been one of the most important application for diagnostic imaging in radiology (1-4).